Comparing the influence of acetate and chloride anions on the structure of ionic liquid pretreated lignocellulosic biomass. (October 2016) - Kim, Hyungsup; Ahn, Yongjun; Kwak, Seung-Yeop
Abstract: The effect of the anion type, in an ionic liquid, on the transition of the crystalline structure when lignocellulose was pretreated in 1-ethyl-3-methylimidazolium acetate (EmimOAC) or 1-ethyl-3-methylimidazolium chloride (EmimCl) was studied. The influence of the pretreatment on the composition, the molecular structure, and the crystalline structure was observed using Fourier-transform infrared (FT-IR) compositional analysis, thermogravimetric analysis (TGA), rheological behavior, and X-ray diffraction (XRD). Compared to EmimCl, EmimOAC pretreatment substantially decreased the lignin and hemicellulose contents. The pretreatment also significantly changed the entanglement or crosslinking state of polymer chains in the lignocellulose solution. The changes in lignin content and the transformation from cellulose I to II were dependent on the anion type of the ionic liquid. The pretreated samples were recrystallized to cellulose II only in EmimOAC, whereas the samples pretreated with EmimCl had both cellulose I and II structures present at the same time. Highlights: Two types of ionic liquids were applied to lignocellulosic biomass pretreatment. Different ionic liquids significantly influenced the characteristics of biomass. The removal efficiency of non-cellulosic components depended on type of ionic liquid and temperature. Well-dissolved biomass was more hydrolyzed than heterogeneous dissolution. Improvement of molecular mobility dramatically changed the crystalline structure.